Media Bermain Balok Warna Untuk Meningkatkan Atensi pada Anak Autis Kelas II SLB Autis Harapan Mandiri Palembang - Syalita, Belva; Arisandy, Desy (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This community service activity was carried out as a form of contribution to support the learning process of children with autism at SLB Autis Harapan Mandiri Palembang through the use of colored block play media. The background of this activity was based on the low level of attention ability of children with autism in following instructions and maintaining focus during structured learning activities. The purpose of this community service was to describe the implementation of colored block play media as an effort to improve focused attention in a second-grade child with autism. The method used involved direct observation and assistance with a qualitative descriptive approach toward one student with the initial R. The activity was conducted over three days through guided play activities using colored blocks and number blocks. The results of the activity indicated that the subject’s ability to maintain attention and follow instructions was still relatively low and did not show a significant improvement within the short duration of implementation. The subject tended to exhibit excessive motor behavior, difficulty in color discrimination, and a limited attention span, although some positive responses were observed, such as occasional eye contact and simple verbal responses. The implications of this community service activity suggest that colored block play media have the potential to serve as an attention-stimulation medium for children with autism when implemented consistently, in a structured manner, and tailored to the child’s sensory needs. The conclusion of this activity is that colored blocks can be utilized as an alternative learning activity in special education services; however, intensive assistance and continuous implementation are required to achieve more optimal outcomes.